2018
DOI: 10.1587/elex.15.20180387
|View full text |Cite
|
Sign up to set email alerts
|

A novel hardware-efficient CPG model based on asynchronous cellular automaton

Abstract: A novel hardware-efficient central pattern generator (CPG) model the dynamics of which is described by an asynchronous cellular automaton is proposed. It is shown that the proposed model can generate multi-phase synchronized periodic signals, which are suitable for controlling a serpentine motion of a snake-like robot. The proposed model is then implemented on a field programmable gate array (FPGA) and is used to control a snake-like robot. It is shown by experimental validation using a prototype machine that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…• Asynchronous CA CPG models [33] [34]. These studies have shown that class CTDS biomimetic models have many advantages, such as the following: (i) The models can be implemented by fewer circuit elements than the numerical integration models employed in digital processors [20]- [34], and (ii) They consume lower power than numerical integration models employed in digital processors [20]- [34]. Hence, this study aims at presenting a novel asynchronous CA model of the CPG that consumes fewer circuit elements and lower power than a conventional digital processor CPG model.…”
Section: Introductionmentioning
confidence: 99%
“…• Asynchronous CA CPG models [33] [34]. These studies have shown that class CTDS biomimetic models have many advantages, such as the following: (i) The models can be implemented by fewer circuit elements than the numerical integration models employed in digital processors [20]- [34], and (ii) They consume lower power than numerical integration models employed in digital processors [20]- [34]. Hence, this study aims at presenting a novel asynchronous CA model of the CPG that consumes fewer circuit elements and lower power than a conventional digital processor CPG model.…”
Section: Introductionmentioning
confidence: 99%
“…It goes without saying that most conventional modeling and implementation methods of neuromorphic circuits have been based on the first, the second, and the third methods [18][19][20][21][22][23][24][25][26][27][28][29][30]. On the other hand, our group and a few other groups have designed neuromorphic circuits based on the fourth method [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 97%
“…CPGs have been mostly modeled by coupled nonlinear oscillators utilizing their synchronization and stability properties, for example, spiking neurons [3][4][5], Van der Pol oscillators [6][7][8], Hopf oscillators [9][10][11], and Kuramoto oscillators [12][13][14]. These models have been applied to gait generation for various types of bio-inspired robots and clinical prosthetic devices [15][16][17][18][19][20][21]. In such models, since one synchronization pattern corresponds to one gait pattern of legged animals, it is required to synchronize from any transient state to a desired pattern (Fig.…”
Section: Introductionmentioning
confidence: 99%